2020
DOI: 10.48550/arxiv.2009.03648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adapted Pepper

Maxime Caniot,
Vincent Bonnet,
Maxime Busy
et al.

Abstract: One of the main issue in robotics is the lack of embedded computational power. Recently, state of the art algorithms providing a better understanding of the surroundings (Object detection, skeleton tracking, etc.) are requiring more and more computational power. The lack of embedded computational power is more significant in mass-produced robots because of the difficulties to follow the increasing computational requirements of state of the art algorithms. The integration of an additional GPU allows to overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has also been reported that Pepper's camera suffers from radial distortion, especially with flat surfaces [32]. Another study [38] added a 3D camera to enhance the capability of Pepper. Tariq et al [39] found that AI algorithms misclassified faces when analyzing South Asian participants, which supports the current study's results related to Pepper's inability to identify Asian participants' faces.…”
Section: Face Detection By Peppermentioning
confidence: 99%
“…It has also been reported that Pepper's camera suffers from radial distortion, especially with flat surfaces [32]. Another study [38] added a 3D camera to enhance the capability of Pepper. Tariq et al [39] found that AI algorithms misclassified faces when analyzing South Asian participants, which supports the current study's results related to Pepper's inability to identify Asian participants' faces.…”
Section: Face Detection By Peppermentioning
confidence: 99%
“…Existing approaches to enhance Pepper's visual perception connected the robot's input and output functions with other visual perception libraries, such as the Robot Operating System. However, existing work has not integrated SOTA online human tracking and pose estimation, limiting its visual perception performance in complex scenarios [3,7].…”
Section: Introductionmentioning
confidence: 99%